Phosphine oxide based polyimides: structure–property relationships. Issue 80 (30th October 2017) - Butnaru, Irina; Bruma, Maria; Gaan, Sabyasachi
Abstract : The PI flame retardance has been influenced by the variation of flexible segments leading to a reduction of THR. Abstract : Several aromatic polyimides containing phosphine oxide moiety and different flexible linkages were synthesized and evaluated for their properties. The influence of flexible units on solubility, optical, wetting, static contact angles, thermal, and dielectric properties, as well as flame retardant behaviour were investigated. The results evidenced an improvement of the physical properties of the synthesized polyimides as compared to the classical aromatic polyimides. Thus, high values of transmittance of 80–88% at 450 nm were obtained, while the static contact angles of water and ethylene glycol were in the range of 74–92° and 52–62°, respectively. The thermogravimetric analysis confirmed that the initial decomposition temperature of these polyimides was in the range of 473–487 °C; they exhibited a single-stage decomposition process in the domain of 492–511 °C and had a residual weight in the range of 49–62% at 800 °C in nitrogen. Glass transition temperatures of the polyimides were in the domain of 216–271 °C strongly depending on the rigidity of the dianhydride segment. The dielectric constant values of thin free-standing films made from these polyimides were in the range of 3.36–3.64, close to those registered for commercially available polyimide (Kapton®). Flame retardant properties of the polyimides showed reduced values for peak heat release rate which were in the range of 27–429 W g −1 and for total heat release in the domain of 1.4–8.3 kJ g −1 .